Environmental DNA Documents Ecosystem‐Wide Biodiversity Within the Marine Protected Area Stellwagen Bank National Marine Sanctuary - Jennifer M. Polinski; Emma L. Strand; Timothy P. O'Donnell; Tammy L. Silva; David N. Wiley; Matthew J. Harke (Environmental DNA)
ABSTRACT Marine protected areas (MPAs) can help ensure long‐term conservation of natural resources and protect biodiversity, ecosystem services, and cultural values in the face of anthropogenic change. However, determining MPA effectiveness is often challenging due to the lack of comprehensive baseline data and/or biases associated with biodiversity survey methods. Environmental DNA (eDNA) represents a promising tool to overcome these challenges. Here, we used a suite of three metabarcoding targets—prokaryote‐specific 16S, eukaryote‐specific 18S, and vertebrate‐specific 12S—to generate baseline data of all organisms, from bacteria to whales, within Stellwagen Bank National Marine Sanctuary (SBNMS). Surface water, bottom water, and sediment from 40 sites revealed three archaeal, 46 bacterial, 22 protistan, and 17 metazoan phyla. eDNA offers insight into the spatial resolution of biodiversity within SBNMS, potentially providing a new tool which could inform management practices to protect biodiversity. For vertebrate eDNA monitoring, most species were observed in bottom water, suggesting that less extensive sampling could be sufficient if targeting overall vertebrate richness. However, the inclusion of other sample types revealed patterns in relative sequence abundance that may be indicative of habitat use, particularly for Northern sand lance, a key forage fish. Microbial, phytoplankton, and zooplankton community composition differed dramatically between sample types, requiring all three to adequately capture species richness, providing data for potential indicator species such as those that cause harmful algal blooms. While future evaluations of cost, sampling scope, frequency, and how to incorporate data into management practices are needed, this study offers important baseline information for new hypotheses testing.